Cu2O-CuO/Chitosan Composites as Heterogeneous Catalysts for Benzylic C−H Oxidation at Room Temperature - Jurin Kanarat (2022)
Recently, in catalysis, chitosan has been exploited as a macrochelating ligand for metal active species due to the presence of various functional groups in its structure. Moreover, copper-based catalysts are classified as one of the most environmentally friendly catalytic systems and their use for the oxidation of alkylarene has not been established much. Therefore, in this work, the hydrothermal synthesis of copper oxide-chitosan composites as heterogeneous catalysts for the benzylic C−H oxidation of alkylarene was investigated. Characterization results reveal mixed phases of CuO and Cu2O, inferring the ability of chitosan to act as a reducing sugar under the hydrothermal condition. The pre-existing interaction between copper species and chitosan as well as the co-existence of the Cu2O and CuO structures give rise to the efficient performance of the catalysts. The synthesized composites exhibit high activity for the oxidation of fluorene to 9-fluorenone at room temperature and small catalyst loading (1 mol % of Cu, >90 % conversion and 100 % selectivity). Superior TOF was observed, and a good scope of substrates can be converted to corresponding ketones in 48–97 % yields with these copper oxide-chitosan catalysts. In addition, the catalysts can be used for up to nine cycles without significant decrease of the activity.